Pelaksanaan Supervisi Kepala Madrasah Dalam Meningkatkan Kinerja Guru Di Madrasah Aliyah Daarul Ulum Sukaraja Garut - Sifa Nurdiani (UNISAN JURNAL, 2024)
This research aims to explore the implementation of supervision by madrasah heads in improving teacher performance at Madrasah Aliyah Daarul Ulum Sukaraja Garut. Supervision by madrasa heads has an important role in ensuring the effectiveness of teaching and learning in madrasas, but has not been studied in depth, especially in the context of Madrasah Aliyah Daarul Ulum Sukaraja Garut. The research method used is a qualitative approach with data collection techniques through interviews, observation and document analysis. Research participants included madrasa heads, teachers and administrative staff at Madrasah Aliyah Daarul Ulum Sukaraja Garut. The results of the research show that the implementation of supervision by the head of the madrasah at Madrasah Aliyah Daarul Ulum Sukaraja Garut has been carried out routinely and in a structured manner. Madrasah heads carry out various supervision activities, such as class observations, reflective discussions, and individual coaching, to help improve teacher performance. However, there are several obstacles faced in implementing supervision, such as limited time, human resources and technological skills. To overcome these obstacles, collaborative efforts are needed between madrasa heads, teachers and other related parties. Keywords: Supervision, Teacher Performance